Case Report: Phenotypic Switch in High-Grade B-Cell Lymphoma With MYC and BCL6 Rearrangements: A Potential Mechanism of Therapeutic Resistance in Lymphoma? - Liu, Hui; Shen, Qi; Chang, Chung-Che; Hu, Shimin (Frontiers in Oncology, 2021)
Lineage switch between myeloid and lymphoid in acute leukemia is well established as a mechanism for leukemic cells to escape chemotherapy. Cross-lineage transformation is also recognized in some solid tumors on targeted therapy, such as adenocarcinoma of the lung or prostate adenocarcinoma that transforms to neuroendocrine carcinoma on targeted therapy. Now lineage plasticity is increasingly recognized in mature lymphomas, such as small B-cell lymphoma transforming to histiocytic/dendritic cell sarcoma. However, there is no report of aggressive mature B-cell neoplasm switching from one histologic category to another upon targeted therapy. We report here a case of high-grade B-cell lymphoma with MYC and BCL6 rearrangements relapsing as a high-grade plasmablastic neoplasm with MYC and BCL6 rearrangements after R-CHOP and R-EPOCH therapy. Being aware of this rare scenario will help improve our understanding of the underlying mechanisms of escape from therapy and progression of lymphoma.